DESIGN OF VISUAL ASSETS AND SUPPORTING ELEMENTS OF THE SAUPGEN GAME - I Wayan Adi Putra Yasa; I Nyoman Jayanegara; I Nyoman Anom Fajaraditya Setiawan (Journal of Aesthetics, Design, and Art Management, 2025)
Purpose: designing character design assets, items, obstacles, and background for the development of the Saupgen game. Research methods: research starts from determining the visual style based on the game concept, media, and user segmentation. After that, visual study processes are collected into a moodboard, brainstorming is carried out to get appropriate visuals in the form of design sketches, and then the visualization stage using a computer/laptop device. Findings: through the process of visual study, brainstorming, and visualization, suitable design assets were obtained in the form of boy character assets in typical. The character assets resulted in a design of a boy wearing traditional Balinese clothing, namely udeng and kamen. The collected letter item assets and obstacle assets used gadgets and game consoles. For the background assets, the chosen atmosphere was a beautiful Balinese rural panorama environment with mountains, coconut trees, and temple buildings. Implications: Obtain game visual assets that are suitable for the children's market segmentation.